Biliary Cystadenoma - A Case Report - Vadamalai, Kopperundevi (Indian Journal of Case Reports, 2016)
Biliary cystadenoma are rare cystic lesions of liver. They accounts for less than 5% of nonparasitic cyst of liver. Hueter first reported biliary cystadenoma in 1887. It is an extremely rare benign hepatic tumor arising from von meyerberg complexes. It occurs frequently in middle age between 40 and 50 years with female preponderance. We, hereby, report a case of 70 year male, who presented with mass and pain in the right upper abdomen.